Industrial-Strength Controlled Concurrency Testing for C# Programs with Coyote - Deligiannis, Pantazis; Senthilnathan, Aditya; Nayyar, Fahad; Lovett, Chris; Lal, Akash (TACAS, 2023)
This paper describes the design and implementation of the open-source tool Coyote for testing concurrent programs written in the C# language. Coyote provides algorithmic capabilities to explore the state-space of interleavings of a concurrent program, with deterministic repro for any bug that it finds. Coyote encapsulates multiple ideas from the research community to offer state-of-the-art testing for C# programs, as well as an efficiently engineered implementation that has been shown robust enough to support industrial use.